Labor selection over the business cycle: An empirical assessment - Brigitte Hochmuth; Hermann Gartner; Britta Kohlbrecher; Christian Merkl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2016)
This paper is the first to analyze how much the probability of selecting a worker from a pool of applicants fluctuates over the business cycle. We use the German Job Vacancy Survey to construct the selection rate on the regional, industry, and national level and show that it is negatively correlated with unemployment. In addition, panel estmations reveal a positive comovement between the selection rate and market tightness, which is in line with the theoretical prediction from labor selection models.
Keywords: E24; E32; J64; 330; Labor Selection; Job-finding Rate; Labor Market Dynamics; Business Cycle